Millennial Generation Preferences for the Use of Technology in Improving Livelihood Experiences in Accommodation Services - Ni Wayan Chintia Pinaria; I Gusti Agung Febrianto; Mayang Fitri Anggani (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: Determine the preferences of the millennial generation towards the use of technology in improving the experience of staying at accommodation services. Method: The data analysis technique used in this research is descriptive statistical techniques using measuring instruments in the form of the Microsoft Excel 2013 computer program. The data collection technique uses a questionnaire. Respondents in this study were domestic (Indonesian) tourists from the millennial generation who were on holiday in Bali with an age range of 20-40 years and had stayed in accommodation facilities for at least 1 year. This research determined a sample size of 100 people. Result: Respondents agreed that the existence of new technology had an impact on respondents' decisions in choosing accommodation to stay. So does the willingness to pay extra for accommodation that has the latest technology. The presence of technology in accommodation facilities has a positive impact on tourists' staying experience. The presence of new technology has an impact on respondents' decisions in choosing accommodation to stay and their willingness to pay extra for accommodation that has the latest technology. The role of technology is very important for the millennial generation in choosing accommodation and is able to provide new experiences for enjoying current accommodation. Contribution: The use of smartphones will become an option to attract the interest of the millennial generation to stay at an accommodation service, especially during the check-in and check-out process. Apart from that, it is also hoped that the millennial generation in this research can use smartphones to open rooms (smartphone applications as room keys). Meanwhile, to control rooms and order food, the millennial generation in this study preferred to use tablets or iPads in hotel rooms